2016
DOI: 10.5424/sjar/2016143-9148
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of Ultisol soil based on interactions between furrow openers and coulters for the no-tillage system

Abstract: The present study evaluated the effect of different associations between coulters and fertilizer furrow openers on soil disturbance, furrow depth and width, according to forward speed. The study was conducted on a farm in Santa Maria (Brazil/RS), in soil classified as sandy loam Ultisol. The experiment consisted of 24 combinations of treatments with three replications in a 2×3×4 factorial experiment. The combinations were formed by the interaction of the factors including: two types of furrow openers (hoe and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
5
10
0
1
Order By: Relevance
“…Compared with 8 W, the A from 13 W, 18 W, and 25 W furrows were reduced by 20.2%, 36.1%, and 22.8%, respectively (Table 3). This conclusion is consistent with Francetto et al [34], who found that when used together with furrow openers, the flat coulters compared with fluted coulters disturbed soil areas by 12.26%. The difference in working breadth led to the difference in furrow width, since a narrower tool created smaller furrows [35].…”
Section: Furrow Cross-sectional Profilesupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with 8 W, the A from 13 W, 18 W, and 25 W furrows were reduced by 20.2%, 36.1%, and 22.8%, respectively (Table 3). This conclusion is consistent with Francetto et al [34], who found that when used together with furrow openers, the flat coulters compared with fluted coulters disturbed soil areas by 12.26%. The difference in working breadth led to the difference in furrow width, since a narrower tool created smaller furrows [35].…”
Section: Furrow Cross-sectional Profilesupporting
confidence: 91%
“…These results are consistent with Zeng and Yang [24]. However, these results are different from Francetto et al [34], which may be because they installed furrow openers at the back of coulters, and the soil-disturbed areas were subsequently affected by the furrow openers.…”
Section: Furrow Cross-sectional Profilesupporting
confidence: 87%
“…The soil disturbance coefficient produced by DISC 3 was the lowest, at 3.91%, followed by DISC 4, DISC 2 and DISC10 with soil disturbance coefficients of 5.90%, 6.28% and 6.81%, respectively. This indicated that the size of biomimetic elements would affect the soil performance of cutting, shear and compaction, as described by Francetto (Francetto et al, 2016). Less soil disturbance could maintain greater soil moisture to facilitate seed growth.…”
Section: Dem Simulationmentioning
confidence: 91%
“…5. The soil swelling rate and soil disturbance coefficient are important indexes to evaluate the soil disturbance characteristics (Francetto et al, 2016). The soil swelling was the elevation area generated by the increase in voids between the soil.…”
Section: Dem Simulationmentioning
confidence: 99%
“…Soil macroporosity plays an important role in the exchange of gases and water in soil (Francetto et al, 2016). One of the major ecological factors influencing soil porosity, especially macroporosity, is the burrowing activity of the earthworm (Maboeta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%